Misinformation in the media and social networks: A violation of migrants’ rights - Andrada-Zurita, Carolina Y. (2025)
This research was carried out using a qualitative methodology with a descriptive scope (Hernández Sampieri et al., 2014). In which, a documentary review of the texts of Laws 23.592, 24.515 and 25.871 from Argentina was carried out to identify strategies used to curb the circulation of false information in the media. Analyses of academic articles and reports by international bodies (IOM, IEO, UN) were also carried out. Among the most important findings we find that it is difficult to enforce the regulations in a total manner without incurring censorship cases, which means in most cases falling into a moral dilemma. The real implications include that migrants' rights should be protected from the dissemination of false information affecting them and, in turn, any accusation of censorship should be curbed; Carrying out actions that allow awareness not only to journalists and communicators, but also to the general public about the importance of managing the good use of information and not to replicate information that is known to be false, distorted or doubtful.